Optimum Efficiency of the Production Line at the Automotive Industry - Ali, A. J. Adham; Razman, Mat Tahar (Universiti Malaysia Pahang, 2012)
Production Line Balancing Problem (PLBP) is one of the most important stages in automobile manufacturing. It is a critical problem in continuous Production Line (PL), and it is one of the difficult optimization problems. PLBP includes many stations concerned with the allocation of tasks to work, where each station contains a number of operations that cooperate to achieve the task work. The main PLBP are: queuing, idling time among stations during the task achievement, and unregulated number of workers among a station, which is an obstacle to the efficient PL. In this paper, the technical constraint was carried out to minimize the queuing problem and regulate the workers by applying hybrid models; Multi-Objectives Model and Genetic Algorithm. The outcome of the mixed models assists to reduce the queuing and the idling time through harmonizing the tasks in each workstation. In addition to balance the distribution of the new workers in order to get the optimal solutions as well as improving the ability of PL with the high production rate.